Dietary Polyphenols as Potential Therapeutic Agents in Type 2 Diabetes Management: Advances and Opportunities - Barik, Sisir Kumar; Sengupta, Srabasti; Arya, Rakesh; Kumar, Surendra; Kim, Jong Joo; Chaurasia, Reetika (Advances in nutrition (Bethesda, Md.), 2025)
Poor dietary intake or unhealthy lifestyle contributes to various health disorders, including postprandial hyperglycemia, leading to type 2 diabetes mellitus (T2DM). Reduction of postprandial glucose concentrations through diet is a key strategy for preventing and managing T2DM. Thus, it is essential to understand how dietary components affect glycemic regulation. Dietary polyphenols (DPs), such as anthocyanins and other phenolics found in various fruits and vegetables, are often recommended for their potential health benefits, although their systemic effectiveness is subject to ongoing debate. Therefore, this review assesses the current and historical evidence of DPs bioactivities, which regulate crucial metabolic markers to lower postprandial hyperglycemia. Significant bioactivities such as modulation of glucose transporters, activation of AMP kinase, and regulation of incretins are discussed, along with prospects for diet-induced therapeutics to prevent the onset of T2DM.